Serviço de vigilância em saúde da UFSM: uma proposta de sistema de gestão para identificação das doenças relacionadas ao trabalho - Santos, Natália San Martin dos (2022)
The Health and Safety Attention Policy for Federal Public Servants directs that accidents and illnesses of civil servants be recorded in the Integrated Subsystem for Servant Health Care, so that it is possible to compile data and plan actions disease and accident prevention and health promotion. Thus, the research aimed to build a proposal for a Management System to help identify work-related diseases for the Health Care Unit of the Federal University of Santa Maria (UFSM). Based on a case study, mixed research, with an integrative review, the work was initially organized with a bibliographical analysis, offering support to the content of this study. The Operational Norm for Server Health presented the types of Management Systems, with their methodological tools that exist and can be worked on in the area of worker health and safety. The second step consisted of obtaining records of licenses for health treatment and work accident licenses from UFSM employees. In the third stage, a questionnaire was applied to professionals working in the health surveillance service at UFSM. The fourth step was to analyze the diseases with the most requests for leave to analyze the health profile of the servants and the questionnaire responses. The results found in the LTS were that professionals in the position of nursing technicians, working at the University Hospital of Santa Maria, are the most affected by the diseases ICD10 F: Severe depressive episode without symptoms psychotics and adjustment disorders. Followed by the ICD10 M diseases: Lumbago with sciatica and Low Back Pain. In the LAS, the position of nursing technician prevailed with the ICD10 S diseases: fracture of the lateral malleolus, contusion of the thigh, dislocation of other and unspecified parts of the shoulder girdle and fracture of the metatarsal bone. Then ICD10 M disease: lumbar pain and lumbago with sciatica. The results of the questionnaire indicated that health professionals know the public servant's health care policy and its objectives; they believe it is important to plan and evaluate service actions, they know little about management tools to achieve work objectives; however, they know the diseases that most affect the institution's servants, and the best-known methods for planning actions at work were the SWOT Matrix, NR 01 and the PDCA Cycle and most answered that continued training was necessary for action in the area. Finally, the Management System implementation product was presented, the SWOT Matrix, the PDCA Cycle and the Management Tree Theory in Occupational Health and Safety were used. In this way, we sought to contribute to the quality of the services provided and to improve the planning of actions to promote health and safety at work at the UFSM Server Health Care Unit.